The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1039/b820985e
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the selection stringency of phage display using a microfluidic device

Abstract: We report the utilization of microfluidic technology to phage selection and demonstrate that accurate control of washing stringency in our microfluidic magnetic separator (MMS) directly impacts the diversity of isolated peptide sequences. Reproducible generation of magnetic and fluidic forces allows controlled washing conditions that enable rapid convergence of selected peptide sequences. These findings may provide a foundation for the development of automated microsystems for rapid in vitro directed evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 23 publications
(22 reference statements)
0
63
0
Order By: Relevance
“…The DNA library design features a central 40-base random domain flanked by two 20-nucleotide PCR primer sites. We subjected the aptamer-bound, targetcoated beads to high-stringency continuous washing at a high flow-rate (50 mL∕hr) within the MicroMagnetic Separation device (MMS), which has been shown to effectively remove weakly and nonspecifically bound molecules (30). After the separation, the external magnets were removed and the beads carrying the selected aptamers were eluted from the device and PCR amplified; finally, we generated ssDNA from the amplicons for use in a subsequent round of selection.…”
Section: Resultsmentioning
confidence: 99%
“…The DNA library design features a central 40-base random domain flanked by two 20-nucleotide PCR primer sites. We subjected the aptamer-bound, targetcoated beads to high-stringency continuous washing at a high flow-rate (50 mL∕hr) within the MicroMagnetic Separation device (MMS), which has been shown to effectively remove weakly and nonspecifically bound molecules (30). After the separation, the external magnets were removed and the beads carrying the selected aptamers were eluted from the device and PCR amplified; finally, we generated ssDNA from the amplicons for use in a subsequent round of selection.…”
Section: Resultsmentioning
confidence: 99%
“…PPC-1 cells were selected as a model because they express high levels of NRP-1, a well characterized receptor that binds and internalizes peptides with C-terminal arginine residues, typically within a consensus context of R/KXXR/K (the C-end Rule or CendR motif) (29)(30)(31). As a negative control, we used phage expressing hepta-glycine (G7), which exhibits negligible binding to PPC-1 cells (28). Upon reaching 90% confluency, the cells were washed twice with phosphate-buffered saline (PBS).…”
Section: Resultsmentioning
confidence: 99%
“…First, due to the fact that the selection is performed within a microchannel, smaller numbers of target cells are required, which allows us to impose highly stringent mass-action selection pressure (e.g., high molar ratios between the library and target cells) (27), yielding peptides with higher affinity. Second, control of the flow rate of fluids within the microchannel provides a continuous and reproducible means for efficiently removing weakly-or nonspecifically-bound phage (28), resulting in low background binding with minimal cell loss. We demonstrate that continuous washing leads to more efficient enrichment of phage displaying high-affinity peptides to the targeted cell-surface marker.…”
mentioning
confidence: 99%
“…Although recent studies on biopanning in large-scale fluidic devices have been shown, they do not address the more time intensive components of the process and thus are not any more amenable to high-throughput multiplexing. 26,27 Here we report for the first time a time-efficient microfluidic approach that allows for simultaneous single-round identification of binding sequences for multiple targets, without any need for bacterial culture.…”
Section: 25mentioning
confidence: 99%